Effect of soil on microbial diversity of flora and fauna in ecosystem - Sharma, Akash; S, Divya M; Goyal, Deepak S; Mishra, Mohit; Shukla, Prashant (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Soil is a complex and dynamic biological system. We are limited in the determination of microbial mediated reactions because present assays for determining the overall rate of entire metabolic processes (such as respiration) or specific enzyme activities (such as urease, protease and phosphomonoesterase activity) do not allow any identification of the microbial species directly involved in the measured processes. The central problem posed by the link between microbial diversity and soil function is to understand the relations between genetic diversity and community structure and between community structure and function. Soil seems to be characterized by a redundancy of functions; for example, no relationship has been shown to exist between microbial diversity and decomposition of organic matter. Generally, a reduction in any group of species has little effect on overall processes in soil because other microorganisms can take on its function. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->